STUDY OF THE NEWTON RAPHSON METHOD IN ANALYZING THE DEPTH OF FLUID FLOW IN THE WASTEWATER CANAL U RPS TKRO SMKN 1 CIRUAS USING THE MATLAB APPLICATION - Susilo, R Dwi Pudji; Tarigan, Kontan; Sudarma, Andi Firdaus; Oktaviani, Ana Nur; Khaerudini, Deni Shidqi; Fitri, Muhamad (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
Abstract--Flow Depth can be defined as channel height or open channel flow depth, is an important parameter in hydraulic calculations and analysis. The depth of flow in the U channel (U channel) of the Student Practice Room (RPS) for Automotive Light Vehicle Engineering (TKRO) at SMKN 1 Ciruas often causes delayed flow congestion and full channels. Sometimes it is dry if only a few students carry out practical use of room practice and use of water and other waste. The aim of this research is to find a solution to this problem, namely by knowing the depth of flow in the channel so that in the future when designing waste water drainage channels it can be designed appropriately and in accordance with the volume of waste released. The method is to calculate the flow depth in the U channel using NEWTON RAPHSON numerical analysis and the Matlab application to determine the flow depth. The calculation result is the depth of water flow in channel U, with water flow discharge Q = 0.016 m3/s, Manning coefficient for roughness of channel walls and base n = 0.025, slope of channel bottom I = 0.003, and width of channel U B = 0.22 m, at The 11th and 12th iterations flow depth = 0.194864 m. The results of manual exact calculations in the 11th and 12th iterations, the error percentage is 0%, meaning that the flow depth is uniform at a water level of 0.194864 m. Calculations using the Matlab application obtained graphs and the iteration steps were slightly different in the 12th and 13th iterations, the flow depth results were the same = 0.194864 m. The initial guess at flow depth(h)=1, the percentage error is 25%, the uniform flow depth of the RPS TKRO SMKN 1 Ciruas U channel is 0.194864 m.Keywords : Depth of flow, NEWTON RAPHSON, Open Channel, U Channel, MATLAB